2018
DOI: 10.1080/15476286.2018.1511675
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding transcript variants of protein-coding genes – what are they good for?

Abstract: The total number of protein-coding genes in the human genome is not significantly higher than those in much simpler eukaryotes, despite a general increase in genome size proportionate to the organismal complexity. The large non-coding transcriptome and extensive differential splicing, are increasingly being accepted as the factors contributing to the complex mammalian physiology and architecture. Recent studies reveal additional layers of functional complexity: some long non-coding RNAs have been re-defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 86 publications
(95 reference statements)
1
44
0
1
Order By: Relevance
“…It has been indicated that circRNA can serve as prognostic biomarkers because of their stable characteristics [32]. Moreover, several works have demonstrated hidden peptides encoded by circRNAs, which will largely broaden our understanding on the cellular physiology functions [33][34][35]. circRNAs have been considered as 'non-coding' elements, and the circRNA translation will provide a new perspective and new horizon for cancer treatment and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that circRNA can serve as prognostic biomarkers because of their stable characteristics [32]. Moreover, several works have demonstrated hidden peptides encoded by circRNAs, which will largely broaden our understanding on the cellular physiology functions [33][34][35]. circRNAs have been considered as 'non-coding' elements, and the circRNA translation will provide a new perspective and new horizon for cancer treatment and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The Variant Effect Predictor annotates mutations using an extensive array of reference data from previously detected mutations, evidence based results, and estimation of biophysical consequences of mutations; and that is what makes VEP an accurate webbased tool. [42] VEP described regulatory consequences for several mutations, including 15 mutations within a coding region, 15 mutations within a non-coding region, 2 mutations within upstream gene, 9 mutations within downstream gene, 1 mutation within non-coding transcript exon, and 2 mutations within 5 prime UTR variant; briefly, mutations within a coding region affect the protein function, while mutations within noncoding regions can significantly affect disease and could be contribute in the phenotypic feature and RNA-binding proteins (RBPs); [52,53] while mutations in the upstream, downstream, 5′-, and 3′-UTRs might affect transcription or translation process. [54] The consequences are shown in (Table 6) while (Figure 2) demonstrates the summary pie charts and statistics.…”
Section: Discussionmentioning
confidence: 99%
“…The Variant Effect Predictor annotates mutations using an extensive array of reference data from previously detected mutations, evidence based results, and estimation of biophysical consequences of mutations; and that is what makes VEP an accurate web based tool.. (39) VEP described regulatory consequences for several mutations, including 10 mutations within coding region, 5 mutations within a non-coding region. briefly, mutations within coding region affect the protein function, while mutations within non-coding regions can significantly affect disease and could contribute in the phenotypic feature and RNA-binding proteins (RBPs);(40, 41) while mutations in the upstream, downstream, 5⍰-, and 3⍰-UTRs might affect transcription or translation process. (42) The consequences are shown in Table(5).…”
Section: Discussionmentioning
confidence: 99%